Ikhtiar dengan Menjaga Keyakinan dalam Pandangan Hadis Nabi Muhammad: Studi Takhrij dan Syarah Hadis - Setiawan, Ahmad Siddiq; Harun, Amrullah; Rahmah, Siti (Jurnal Riset Agama, 2024)
This article aims to discuss how John Wansbrough's thought views on the Qur'an, the influence of his thoughts in the study of the Qur'an and how other orientalists and Muslim scholars assess the results of his thinking. This research uses a qualitative approach with a literature review. The results of this study show that John Wansbrough is a controversial orientalist because of his opinion about the Qur'an which is skeptic-revisionist. He revealed that the Qur'an is a continuation of the Christian and Jewish traditions or nothing more than a copy or imitation of the bible. The Qur'an according to him is a literary work, besides that he also considers that the activity of copying the Qur'an into manuscript during the reign of Abu Bakar and Usman is just a fictitious. Wansbrough's view is the result of his study of the Qur'an through the analytical approach of literary and historical criticism, which is taken from the methods of criticism commonly used in criticizing the bibles. Many Western and Muslim scholars in responding to Wansbrough's thoughts criticized but some supported him. Nonetheless, Wansbrough's methods and thoughts are enough to contribute to the development of critical methodology in the study of al-Qur'an studies and its interpretation.